Dead funny : the humor of American horror - Gillota, David, 1977- (Rutgers University Press, 2023)
"Horror films strive to make audiences scream, but they also make them laugh. Little work has been done, however, to explain precisely how horror's humor operates. Dead Funny: The Humor of American Horror offers a road map of key humorous devices that have been prominent in North American horror films since the 1930s. Author David Gillota argues that horror's humor does not operate as simple "comic relief" but instead functions in tandem with horror elements. Using humor theory to read horror, Gillota provides insight into several aspects of the genre that have long preoccupied critics: the figure of the monster, imperiled bodies, or gender and racial politics. In doing so, Dead Funny offers analysis of a vast array of films, including classic monster movies, effects-driven splatter films, and recent critical favorites like Get Out and Midsommar. The result demonstrates that humor is and has long been an integral part of the horror genre"--